Nextland. Zeitgenössische Landschaftsarchitektur in Österreich. Contemporary Landscape Architecture in Austria. - (:unkn) unknown (Birkhäuser, 2015)
Österreichische Landschaftsarchitektur wird international wahrgenommen. Nextland zeigt, wie vielfältig die Aufgaben und wie einfach und aufregend gelungene Gestaltungen sein können. Das reich illustrierte Buch portraitiert 188 Freiräume der letzten zwei Jahrzehnte und ergänzt sie mit einem Fotoessays sowie Essay europäischer Fachleute, die den historischen Kontext herstellen und den Status der Landschaftsarchitektur in Österreich kommentieren.

When developing a design concept in a realizable plan, landscape architects oscillate between two different levels of criteria: the tangible design task in context with the planning typology of the park, playground, outdoor swimming pool, or sports facilities, and the individual elements such as steps, ramps, pathways, fenced-in enclosures, outdoor furniture, and so on. "Planning Landscapes" is a well-conceived tool for the planner, which focuses on the two main aspects of "elements" and "typologies." The planner can flexibly shift between these two according to the specific criterion. The publication presents all information relevant to the planning in a detailed, clear, and cohesive manner. These two main chapters are flanked by an introductory chapter explaining the basics and determining factors of designing in open spaces at the front of the book, and the "reference work" at the end of the book where general dimensions and units, specifications and norms are all clearly compiled.
Keywords: Landschaft; Landschaftsplanung; Landschaftsgestaltung; Gartengestaltung; Platzgestaltung; Bestandsaufnahme; Landschaftsarchitektur